Effect of Apical Preparation on Different Needle Depth Penetration. - Samara Gurgis Essa; Razawa Kareem Saeed; Diyar Khalid Baker (Erbil Dental Journal)
Introduction: Irrigation is a fundamental part of endodontic debridement as because it allows for cleaning beyond what might be accomplished by root canal instrumentation. The flushing action produced by the irrigant and the penetration of the irrigant is not dependent only on the anatomy of the root canal system, but also on the depth of placement, system of delivery, the volume and fluid properties of the irrigant. Aim: The aim of the study was to evaluate the effect of apical preparation on the penetration depth of different types of needles.